IMPACT ASSESSMENT OF REAL-WORLD LARGE-SCALE OIL AND GAS PROJECTS WITH FUZZY DATA - Abilez, Almat; Madiyarova, Tomiris; Safin, Serzhan; Tagay, Adilet (School of Engineering and Digital Sciences, 2023)
The proposed capstone project aims to address the limitations of current MCDA methods and develop a more effective tool for decision-making in the oil and gas industry, particularly oilfield selection. The project will focus on the application of three MCDA methods: SPOTIS, COMET, and MCDA Index Tool. These methods will be evaluated based on their ability to address the challenges specific to the oil and gas industry, including various factors. The study will also explore the feasibility of developed comprehensive tool that can effectively address all the criteria required for generating valid results. This tool will be tailored to the unique characteristics of the oil and gas industry, and it will incorporate the various objectives and criteria that are essential for making informed decisions in this sector. The project will utilize a combination of literature review and case studies to investigate the effectiveness of the three MCDA methods and their applicability for the oil and gas industry. The study will also explore the factors that need to be considered in the development of the decision-making tool in this industry, including the availability and quality of data, the level of uncertainty and risk, and the stakeholder preferences. The expected outcomes of this project include a deeper understanding of the challenges and limitations of current MCDA methods in the oil and gas industry, as well as insights into the potential for developing a more effective and comprehensive tool for decision-making in this sector. The results of this study could have significant implications for the oil and gas industry, as well as for other industries that require a systematic approach to decision-making.
Keywords: type of access: restricted access; MCDA; O&G Industry; MCDA Index Tool; SPOTIS; COMET